“Potential Soft Power” as a Resource of Political Influence - V G Ivanov (RUDN Journal of Political Science, 2016)
The author introduces the concept of “potential soft power”, indicating the potential (real or imaginary) of “soft power” influence of political actors, which they do not plan to use directly in a situation of political confrontation, but seek to capitalize on in order to influence the behavior of the opponent. The main objectives of “potential soft power” are deterrence, demoralization and reducing of the space of possible behavior of other parties (both opponents and allies). Certain propositions and statements of the concept of potential power of the economist and mathematician T. Schelling are applied to the perspective of “soft power” in world politics.